Hyperparathyroidism in patients with primary aldosteronism: cross-sectional and interventional data from the GECOH study - Pilz, Stefan; Ritz, Eberhard; März, Winfried (The journal of clinical endocrinology & metabolism, 2012)
Context:. Experimental studies suggest that aldosterone induces hypercalciuria and might contribute to hyperparathyroidism.Objective:. We aimed to test for di
First published online October 19, 2011
Gesehen am 30.10.2018